(untitled) (Medico Legal Update, 2021)
Introduction: Resistance to antibiotics has emerged recently due to the misuse of antibiotics and is a threat to the health?care system, especially in developing countries like Iraq where there are no antimicrobial stewardship programs in most intensive care units (ICU). Materials and Method: This was anobservational, cross-sectional study done in the ICU of Ghazi AL Hariri hospital, Medical City/Iraq. All patients getting admitted to ICU from both genders were included in the study.Samples taken for culture and sensitivity tests included blood, urine, tracheostomy tube, sputum, cerebrospinal fluid, central venous line, and bedsore swab. Results: 43 patients satisfied the inclusion and exclusion criteria and were included in the study. The most common isolated pathogens were pseudomonas in sputum and blood samples, Acinetobacter in wounds and operation skin site infection, Klebsiella in central venous line, and bedsore swab, while Candida in the urine. Klebsiella was the most frequently isolated in overall culture results, it was most sensitive to imipenem, meropenem, and amikacin. Conclusion: Ceftriaxone was the most commonly used antibiotic as an empiric treatment followed by meropenem and amikacin. Most of the isolated pathogens (> 90%) had resistance to ceftriaxone. ICUacquired Klebsiella, P. aeruginosa, and Acinetobacter predominate hospital-acquired infections.